SOCIAL PSYCHOLOGICAL FOUNDATIONS OF CREATIVITY - Botirov, Zoir (Educational Research in Universal Sciences, 2024)
This article discusses the study of creativity in adolescents and its individual characteristics, the formation of creativity in adolescents, strategies that develop creativity, and the socio-psychological basis of creativity.